Rural Territorial Development : The Milk Territory in Southern Chile - Escobar, German (World Bank, 2012)
The milk territory in Southern Chile is studied to examine the evolution of the dairy industry, which was expected to fail when Chile became an associated member of the MERCOSUR regional agreement, and to understand the evolution of the milk territory associated with the dairy industry. The major and most important conclusion of this analysis is that the Chilean dairy industry did not collapse as expected. On the contrary, it has been strengthened by accessing external specialized markets in countries outside the MERCOSUR region. This case is an example of an industry that takes advantage of an open economy and a regional trade agreement to grow, improve competitiveness and impact the territory in which it is settled.